Implementing genomic medicine in clinical practice for adults with undiagnosed rare diseases - Jong Hyeon Ahn; Jihoon G. Yoon; Jaeso Cho; Seungbok Lee; Sheehyun Kim; Man Jin Kim; Soo Yeon Kim; Soon-Tae Lee; Kon Chu; Sang Kun Lee; Han-Joon Kim; Jinyoung Youn; et al. (npj Genomic Medicine)
Abstract The global burden of undiagnosed diseases, particularly in adults, is rising due to their significant socioeconomic impact. To address this, we enrolled 232 adult probands with undiagnosed conditions, utilizing bioinformatics tools for genetic analysis. Alongside exome and genome sequencing, repeat-primed PCR and Cas9-mediated nanopore sequencing were applied to suspected short tandem repeat disorders. Probands were classified into probable genetic (n = 128) or uncertain (n = 104) origins. The study found genetic causes in 66 individuals (28.4%) and non-genetic causes in 12 (5.2%), with a longer diagnostic journey for those in the probable genetic group or with pediatric symptom onset, emphasizing the need for increased efforts in these populations. Genetic diagnoses facilitated effective surveillance, cascade screening, drug repurposing, and pregnancy planning. This study demonstrates that integrating sequencing technologies improves diagnostic accuracy, may shorten the time to diagnosis, and enhances personalized management for adults with undiagnosed diseases.